IMPACT OF PROVIDING CONTENT MASTERY SERVICES FOR THE DISCOVERY LEARNING MODEL APPROACH TO IMPROVE STUDENTS' QUESTIONING SKILLS IN THE LEARNING PROCESS IN SCHOOLS - Hengki Yandri; Masnur Alam; Dosi Juliawati; Sabri Sabri (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
The inability to ask students in the learning process indicates that students do not have good questioning skills. It will hinder students in understanding the subject matter and achievements at school. This study aims to improve students' questioning skills in the learning process by using content mastery services using the discovery learning model. The type of research used is a quantitative experimental approach with a one-group pretest-posttest design. The subjects in this study were 27 people with low questioning skills in the Nurul Haq Semurup Islamic Boarding School students. The data is obtained by spreading a scale of questioning skills developed by researchers who have been tested for validity and reliability. Then the results of the study are processed using the -t-test formula. The results of this study show a significant influence on students' questioning skills before and after being given content mastery services with a discovery learning approach. This means that content mastery services with a discovery learning approach can be used to improve students' questioning skills in the learning process.